Gait Disturbance ... of Red Herrings, Oranges, and Lemons - A Case of Missed Vitamin C Deficiency and Lessons Learnt - De Battista, Nadine Anne; Zammit, Marie Claire; Soler, Sandro Galea; Attard, Stephen (Acta medica (Hradec Kralove), 2023)
Vitamin C deficiency resulting in scurvy, is considered to be a rare nutritional disorder in developed countries, thus leading to underdiagnosis with exposure to unnecessary investigations and delay in appropriate treatment. The wide myriad of clinical signs and symptoms with which vitamin C deficiency can present (including haematological, musculoskeletal and vague constitutional symptoms that overlap with other common medical conditions), also contributes to this diagnostic challenge. Despite scurvy being habitually thought to be present in children with neurodevelopmental conditions such as autism spectrum disorder, other important at-risk groups that frequently tend to be forgotten include children with persistent fussy eating behaviour, and children with abnormal vitamin C metabolism. We hereunder present a case of a 10-year-old boy who presented to an acute general hospital for further investigation with gait disturbance. The lack of detailed nutritional assessment on presentation in the first instance led to a missed diagnosis of vitamin C deficiency, thus exposing the child to a wide array of unnecessary investigations and treatments. The added perplexity to the case resulting from false positive results of investigations performed as part of this child's workup, is also discussed.
Keywords: nedostatek vitaminu C; chůze (způsob); mužské pohlaví; Ascorbic Acid; lidé; Child; dítě; Male; Autism Spectrum Disorder; Ascorbic Acid Deficiency; poruchy autistického spektra; Scurvy; Gait; kyselina askorbová; Citrus sinensis; Humans; pomerančovník čínský; kurděje